Evaluasi Prospek Bisnis Start-Up Digital: Kajian Kualitatif Aspek Pasar, Teknis, Dan Manajemen - Wini Yuliani; Wina Yuliana; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to evaluate the prospects of digital start-up businesses through a comprehensive feasibility analysis with a focus on three main aspects: market, technical and management. The study uses a qualitative approach with data collection methods through in-depth interviews, participant observation and documentation studies. The research informants consisted of 15 digital start-up actors, 5 investors and 3 digital industry experts who were selected using purposive sampling techniques. Data analysis was carried out using the Miles and Huberman technique including data reduction, data presentation, and drawing conclusions. The research results show that from a market aspect, digital start-ups have significant growth potential supported by increasing internet penetration and changes in consumer behavior towards digital. From a technical aspect, it was found that technological infrastructure and product development capabilities are critical factors in determining the success of a start-up. Meanwhile, from a management aspect, the competence of the founding team, monetization strategy, and ability to manage funding determine business sustainability. The main challenges faced include high customer acquisition costs, limited digital talent, and intensifying competition. This research provides theoretical contributions in developing a model for evaluating the viability of digital start-up businesses as well as practical implications for entrepreneurs, investors and policy makers in developing a sustainable start-up ecosystem. The limitation of this research lies in its limited geographic focus, so further research is recommended to expand regional coverage and conduct comparative analysis between digital industry sectors.